Comportamiento de Lima Tahití (Citrus latifolia Tan.) en portainjertos híbridos - Beltran, Victor Manuel; Torrez, Diomede; Dominguez, Carlos; Cardozo, Gustavo Daniel; Garavello, Miguel Fernando (Asociación Argentina de Horticultura (ASAHo), 2024)
Poster